Key Technology and Application of Next-Generation UICC with Remote Management Capability - Ling Han; Minxia Gu; Binfeng Yan; Wei Kuang (Dianxin kexue, 2015)
Supporting remote management will be one of the key technologies of next-generation UICC.The relative research developments of remote management of UICC were introduced.The key technology of eUICC with remote management capability was analyzed.The service model,scenes and business model of UICC were discussed.Finally,a feasible service architecture based on operator's network architecture and typical business requirements was proposed.The architecture provides an exploration and practice for further study and large-scale commercial of UICC with remote management capability.